The allure of otherness: transnational cult film fandom and the exoticist assumption. Issue 1 (2nd January 2017) - Sexton, Jamie
Abstract: Academic scholarship addressing transnational cult fandom, particularly Western cult fans forming attachments to films outside their cultures, has frequently addressed the issue of exoticism. Much attention has been paid to how Western fans are problematically drawn to artefacts outside of their own cultures because of exotic qualities, resulting in a shallow and often condescending appreciation of such films. In this article, I critique a number of such articles for merely assuming such processes without proffering sufficient supporting evidence. In fact, I argue that a number of such exotic-oriented critiques of transnational cultism are actually guilty of practising what they preach against: an insufficient contextualization of fandom and a tendency to downplay the messiness of empirical data in favour of generalized abstractions. Further, I argue that the constant critique of fans as avoiding contextualization has not only been overstated but stringently used as a yardstick to denigrate fan engagements with texts as improper. As such, fans are often 'othered' within such articles, a process mirroring the ways they are accused of othering distant cultural artefacts.